Investigating precise control pathway for haemostatic clip usage in laparoscopic cholecystectomy based on patient clinical variations: an exploratory retrospective observational study - Yu Liu; Xiaodong Wang; Wei Du; Ang Li; Ling Yan; Ying Zhao; Xiru Yu; Jiao Su; Wenqi Zeng (BMJ Open)
Objectives To explore a precise control pathway based on patient clinical variations for haemostatic clip usage in laparoscopic cholecystectomy (LC) through on-site research data from a teaching hospital. Specifically, the study aimed to: (1) to calculate the optimal haemostatic clip consumption in LC based on diagnostic grouping and surgical combinations, and (2) to provide evidence for cost containment of high-value medical consumables used in LC.Design Retrospective observational study.Setting Hospital in southwest China.Participants The inclusion criteria were set as inpatients whose medical records included International Classification of Diseases codes 1–3 with code 51.2300 (corresponding to LC surgery) and who were discharged on medical advice. A dataset containing 1001 patients without any haematological diagnoses was collected.Primary and secondary outcome measures Two ordered multinomial logit models were established to identify factors affecting haemostatic clip use in LC. Two-step clustering was used to form subgroups. The premodel included preoperative variables (acute cholecystitis and scarring/fibrotic atrophy), while the full model added intraoperative variables (anatomical variation and severe adhesions). Both models met application prerequisites.Results Key factors influencing haemostatic clip usage were identified, including acute cholecystitis, scarring/fibrotic atrophy, anatomical variation and severe adhesions. Consumption references for haemostatic clips were established for LC patients with good prognoses on discharge. The ordered multinomial logit model revealed that acute cholecystitis decreased the odds of using four or more clips (p<0.001), while anatomical variation, scarring/fibrotic atrophy and severe adhesions increased the odds (p<0.001 for all). The model suggested using no more than three clips in 17.30% of cases, precisely four clips in 81.72% of cases and five or more clips in 0.98% of cases, depending on the co-occurring factors. Model-predicted clip usage was consistent with actual usage (consistency=0.56).Conclusions This study provides a framework for evidence-based consumable management in LC, demonstrating the potential for extrapolation to other consumables and surgical combinations. Continuous monitoring and timely adjustment will be imperative as medical products and practices evolve.